Hornhautvernetzung beim Keratokonus: "Epi-off" oder "Epi-on"? - Raiskup, F; Veliká, V; Veselá, M; Spörl, E (Klinische Monatsblatter fur Augenheilkunde, 2015)
Corneal cross-linking can halt the progression of keratoconus, but what is the best approach for treatment? There are a number of treatment options for keratoconus, but only corneal cross-linking (CXL) appears to halt the progression of the disease. To guarantee effective cross-linking, CXL treatment involves removal of the corneal epithelium prior to riboflavin application and ultraviolet light illumination - "epi-off" CXL. Several methods of "epi-on" (transepithelial) CXL have been proposed, such as keeping the corneal epithelium intact which should be less painful and help avoid other CXL-associated adverse events. The evidence so far is that epi-off CXL remains the most effective method of strengthening the cornea and slowing keratoconus progression - but transepithelial methods are gaining ground.
Keywords: kombinovaná terapie; výsledek terapie; Keratoconus; lidé; Photochemotherapy; riboflavin; Ultraviolet Therapy; Photosensitizing Agents; Treatment Outcome; Cross-Linking Reagents; fotosenzibilizující látky; reagencia zkříženě vázaná; Combined Modality Therapy; medicína založená na důkazech; rohovkový epitel; Epithelium, Corneal; terapie ultrafialovými paprsky; fotochemoterapie; keratokonus; Evidence-Based Medicine; Riboflavin; Humans